Essential fragmentation metrics for agricultural policies: Linking landscape pattern, ecosystem service and land use management in urbanizing China. (June 2020) - Wei, Lai; Luo, Yun; Wang, Miao; Su, Shiliang; Pi, Jianhua; Li, Guie
Abstract: Fragmentation, as one of the most distinct characteristics of agricultural landscapes worldwide, has resulted in a diversity of ecological consequences. It remains as a gap in the literature on how provisioning service changes in association with agricultural fragmentation and land use management. Addressing such a gap at a national level should provide essential insights for policymakers. This paper identifies the essential metrics from a set of landscape metrics for describing agricultural fragmentation and further develops an integrated fragmentation index (IFI). Using the IFI, spatiotemporal dynamics of agricultural fragmentation across Chinese cities from 2010 to 2017 are captured. In particular, an increasing trend of fragmentation is identified and southern China is characterized by more fragmented agricultural landscapes than the other parts. Spatial regression, with the Cobb-Douglas Production Function as the theoretical basis, is employed to quantify the relationships among provisioning service, agricultural fragmentation, and land use management. It is discovered that landscape fragmentation would impair the supply of the provisioning service and sustainable land use management regulates the provisioning service in a positive way. We argue that alleviating the landscape fragmentation issue would not be achieved with simple measurement. Cooperation of a series of administrative acts, such as land reclamation, land use transfer, household registration system reform and improvement of employment and welfare system, should be fundamental and practical approaches. The present study demonstrates a novel methodological framework to unravel the effect of agricultural fragmentation on provisioning services, which should be useful for understanding the complex human-ecosystem interactions. Research Highlights: Essential metrics for describing China's agricultural fragmentation are identified. An integrated fragmentation index (IFI) is developed for Chinese prefecture-level cities. Spatiotemporal dynamics of agricultural fragmentation across China are captured. Relationships are quantified among provisioning service, agricultural fragmentation, and land use management.